Microbial Transformations of 7-Hydroxyflavanone - Edyta Kostrzewa-Susłow; Tomasz Janeczko (The Scientific World Journal)
Microbial transformations of racemic 7-hydroxyflavanone using strains of genus Aspergillus (A. niger KB, A. niger 13/5, A. ochraceus 456) and the species Penicillium chermesinum 113 were studied. The products of O-methylation, O-methylation along with hydroxylation at C-3′ and C-4′, reduction of the carbonyl group, reduction of the carbonyl group along with hydroxylation at C-5, and dehydrogenation of C-2 and C-3 were obtained. Most of the products (with the exception of the O-methylation one) have stronger antioxidant properties than the initial substrate.